2021
DOI: 10.3892/mmr.2021.12026
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA ABCB10 promotes cell proliferation and invasion, but inhibits apoptosis via regulating the microRNA‑1271‑mediated Capn4/Wnt/β‑catenin signaling pathway in epithelial ovarian cancer

Abstract: Circular RNA ABCB10 (circ-ABCB10) modulates cellular functions and microRNA (miR)-1271 in epithelial ovarian cancer (EOC). The present study aimed to investigate the interaction between circ-ABCB10 and miR-1271 in regulating EOC cellular function and the calpain small subunit 1 (Capn4)/Wnt/β-catenin signaling pathway. circ-ABCB10 and miR-1271 expression levels were detected in EOC cells (OVCAR3, UWB1.289, SKOV3 and CAOV3) and normal ovarian epithelial cells (IOSE80) via reverse-transcription quantitative PCR. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Breast cancer is a common type of cancer worldwide, which still ranks as the second most prevalent leading cause of cancer-related mortality among females ( 62 , 63 ). ARID1A plays an important pathobiological role in breast cancer, and the partial loss of its expression is associated with unfavorable outcome in patients with breast cancer ( 64 ).…”
Section: Tumor Suppression By Arid1amentioning
confidence: 99%
“…Breast cancer is a common type of cancer worldwide, which still ranks as the second most prevalent leading cause of cancer-related mortality among females ( 62 , 63 ). ARID1A plays an important pathobiological role in breast cancer, and the partial loss of its expression is associated with unfavorable outcome in patients with breast cancer ( 64 ).…”
Section: Tumor Suppression By Arid1amentioning
confidence: 99%
“…Ovarian cancer (OC), endometrial cancer (EC), and cervical cancer are the three most common gynecological malignancies [271][272][273][274]. The expression of circ-ABCB10 is significantly upregulated, while circPLEKHM3 expression is downregulated in OC [184,220]. Moreover, the level of circPLEKHM3 is positively associated with the overall survival rate in patients with OC [184].…”
Section: Female Reproductive System Cancersmentioning
confidence: 99%
“…Moreover, the level of circPLEKHM3 is positively associated with the overall survival rate in patients with OC [184]. Circ-ABCB10 remarkably facilitates cell proliferation and invasion and reduces cell apoptosis by miR-1271 in OC [220]. Circ-ABCB10 plays a critical role in OC progression via the regulation of Capn4/Wnt/β-catenin.…”
Section: Female Reproductive System Cancersmentioning
confidence: 99%
“…Among the target miRNAs that can be regulated by circRNAs, it was demonstrated that miR-1252 can provide potential biomarkers and therapeutic targets in non-small cell lung cancer (Tian et al, 2019) and epithelial ovarian cancer (Chen et al, 2019). Similarly, it was also found that circ-ABCB10 can sponge miR-1271, which may have a complementary sequence, possibly regulating cell proliferation and migration of breast cancer and epithelial ovarian cancer cells (Liang et al, 2017;Lin et al, 2021;Zhao et al, 2021). Furthermore, since conserved miR-1271 target sites on circ-ABCB10 are complementary to miR-1271, these sites could be a lodging site for transport (Lin et al, 2021).…”
Section: Circ-abcb10 Functions As a Mirna Spongementioning
confidence: 99%